A Phenomenological Analysis on Chosen Surah Recitation before and after Sampan Making in the Hamlet of Sarotak Sumenep - Masodi; Delta Yaumin Nahri (Universitas Islam Negeri Madura, 2026)
The study of the Qur'an has undergone significant development, extending into socio-cultural aspects that involve the community as both subject and object. This article examines a religious ritual in the form of a sampan making ceremony in the hamlet of Sarotak, Poteran Village, Talango District, Sumenep Regency. This study uses a descriptive qualitative method with Edmund Husserl's phenomenological analysis. This study found that, first, the origins of the salametan sampan tradition are unknown, as this tradition is part of the cultural heritage passed down by ancestors. Second, there are two stages in the salametan ritual: the first stage is called “makabin sampan” and the second stage is called “matoron sampan.” During both rituals, selected surahs from the Qur'an are recited. Surah an-Nūr, al-Qalam, al-Waqi'ah, Yasin, and ar-Raḥmān are the most popular surahs. Third, the meaning of reciting selected surahs in the salametan tradition is essentially as a means of striving for the sampan that will be used to seek sustenance to obtain blessings and safety. Phenomenological reduction analysis explains that the tradition of salametan sampan making is a dynamic religious practice as a form of spiritual action. Its eidetic reduction is to give thanks and ask for blessings, while also creating a sense of community and solidarity among the Sarotak people. Its transcendental reduction states that the salametan sampan is an effort to get closer to God, ask for safety, and hope for His blessing.